Development of a mentee behaviour scale for workplace mentoring partnerships - Jennifer K. Giancola; Iwan D. Webster; Jack C. Friedrich; Thomas E. Burroughs (International Journal of Evidence Based Coaching and Mentoring)
Workplace mentoring has typically focused on mentor functions without sound measurement of mentees. This study developed and tested a mentee behaviour scale (MBS) to assess mentors’ and mentees’ perceptions of effective mentee behaviours. The construct and items were derived from the literature and our experience implementing workplace mentoring programmes. An expert panel evaluated content validity before testing the MBS on an employee sample of 295 mentees and 294 mentors. Using a multistep analysis, the MBS was reduced to 24-items with mentee and mentor versions. Results supported MBS reliability and validity for use in workplace mentoring research and practice.